Mapping soil nutrients and texture for the pilot project of glutinous rice variety Pulut Siding (MR 47) in Langkawi Island, Malaysia - Muhammad Naim, F. A. R.; Amir Hamzah, A. G.; Amelia, A. J.; Nurul Syakira, S.; Mohamad Najib, M. Y.; Azzami Adam, M. M.; Ahmad Arif, I.; Shahida, H.; Mohd Shahril Shah, M. G. (International Journal of Agricultural Technology, 2024)
The soil nutrient and texture status in four rice areas, namely Kg. Ayer Hangat, Kg. Batu Duyung, Kg. Baru/Teluk, and Kg. Ulu Melaka on Langkawi Island, Malaysia was successfully analysed using Geographic Information System (GIS) techniques. The results indicated no significant variations in organic carbon, cation exchange capacity (CEC), and conductivity among the study areas. However, distinctive differences were observed in soil chemical features, including pH values, total nitrogen, available phosphorus, and exchangeable potassium—specifically, the rice fields in Kg. Ayer Hangat exhibited a significantly lower pH (4.68) compared to Kg. Batu Duyung (5.23) and Kg. Baru/Teluk (5.09). Total nitrogen content was notably higher in Kg. Ayer Hangat (0.18). Available phosphorus showed significant variations, with Kg. Batu Duyung recorded the highest (37.32 mg/kg) and Kg. Ayer Hangat is the lowest (15.25 mg/kg). Exchangeable potassium levels were markedly higher in Kg. Ulu Melaka (0.53 cmol(+)/kg) compared to Kg. Ayer Hangat (0.29 cmol(+)/kg), while Kg. Batu Duyung and Kg. Baru/Teluk recorded lower levels (0.19 cmol(+)/kg and 0.08 cmol(+)/kg, respectively). Furthermore, Soil Taxonomy (ST) was employed to categorize soils, with the majority falling under hydrologic soil group A, primarily sandy loam types. Kg. Ayer Hangat, however, was categorized under hydrologic soil group C (sandy clay loam). The study suggests that additional research may be conducted to assess the practical implementation of soil nutrient mapping and texture in small plantation systems. This could potentially bridge the gap between research findings and practical applications